EFEK KOMPENSASI TERHADAP KINERJA PEGAWAI MELALUI KUALITAS SDM SEBAGAI VARIABEL INTERVENING PADA KANTOR PERBEKEL KECAMATAN BATURITI: The Effect Of Compensation On Employee Performance Through The Quality Of Human Resources As Intervening Variables At The Baturiti District Perbekel Office - Noval, I Made Mai; Adnyana, I Putu Agus; Arta, I Ketut Budi Dana (Ganec Swara, 2025)
The goal of this study is to examine the relationship between salary and employee performance at the Baturiti District Head Office by controlling for human resource quality with an intervening variable. This study employs a quantitative approach. Forty individuals from the Baturiti District Office participated in the data collection process, which involved administering a questionnaire with an agree-disagree scale and utilizing a variance-based structural equation model, also called SEM or PLS-SEM. The study’s findings show that pay has an effect on performance, which in turn has an effect on HR quality, and HR quality has an effect on performance. With that in mind, the Baturiti District Office should prioritize raising salaries and enhancing HR quality in order to boost employee performance as part of its realization. Future efforts to improve Human Resource Quality and raise salaries at the Baturiti District Office can be better understood with the help of this study